Symptomatic Tarlov Cysts: an MRI evaluation of case series and literature review - Rana, Netra; Ma, Shao Hui; Zhang, Ming; Dahal, Subesh; Min, Zhi-Gang (Asian Journal of Medical Sciences, 2013)
Corrections: on Page 38 in the 4th line of text, the information in brackets (Figure 1, 2, 3a and 4) was replaced on 24th June 2013 with (Figure 1. 2 3b and 4). The number of the references has also been changed. The corrected PDF is available by clicking the link below. Aim: To analyze the characteristics of symptomatic Tarlov cysts by MRI. Materials and Methods: Neuroimaging and clinical outcome data were reviewed of 48 consecutive patients treated for symptomatic Tarlov cysts. All patients were scanned under Philips Gyroscan Intera 1.5T scanner with spinal surface coils. Two widely used surgical procedures were performed, 1) incision and drainage of the cyst with imbrication of the redundant nerve root sheath, and 2) exposure of the cyst, drainage of cyst contents, identification of nerve roots, and cyst wall resection combined with duraplasty. The post-operation follow-up was obtained from return visits to the neurosurgery and orthopaedic out-patient department or by telephone questionnaires. Results: All cystic lesions showed hypointense signal intensity on T1WI and hyperintense signal intensity on T2WI, but the nerve root showed iso-intensity on T1WI and low signal intensity on T2WI. They were linear in shape on sagittal view, and hypo intense dotted spots within the cysts on traverse view. Surrounding structures of the larger cysts were compressed and had bone erosions in some cases; the spinal canal and the intervertebral foramen on the affected side were enlarged. The lesions/cyst wall showed no enhancement after gadolinium administration. Conclusion: MRI will give a definite diagnosis of Tarlov cysts if nerve root presents within the cyst cavity or in the cyst wall; eliminating the need for histological confirmation. A correct analysis of the characteristics of symptomatic Tarlov cysts by MRI, will document its usefulness in noninvasive diagnosis and aid in exploration of the simplest treatment method. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8056 Asian Journal of Medical Sciences 4(2013) 35-42